Dataset for "How to administer an antidote to Schrödinger’s cat" - Alvarez Velasquez, J; IJspeert, M; Barter, O; Yuen, B; Barrett, T D; Stuart, D; Dilley, J; Holleczek, A; Kuhn, A (University of Oxford, 2021)
Experimental data gathered in laboratory, recorded by Single Photon Counting Modules.